Build-up and chronology of blue ice moraines in Queen Maud Land, Antarctica - Akçar, Naki; Yeşilyurt, Serdar; Hippe, Kristina; Christl, Marcus; id_orcid:0 000-0002-3131-6652; Vockenhuber, Christof; Yavuz, Vural; Özsoy, Burcu (Elsevier, 2020)
Blue ice moraines are common supraglacial landforms in Antarctica and they are considered to record the ice volume fluctuations. In this study, we use photogrammetry and the analysis of multiple cosmogenic nuclides (10Be, 26Al, and in-situ 14C) in boulders on three blue ice moraines to explore the timing of ice volume fluctuations in the Sør Rondane Mountains, Queen Maud Land, and provide insights into the role of sediment sources in the reconstruction of their chronology. In the field, we observe that the blue ice moraines are composed of subglacially and supraglacially transported sediments. Cosmogenic 10Be and 26Al exposure ages of 14 surface samples, collected from boulders on three blue ice moraines, range from 15.4 ± 1.1 to 659.5 ± 33.9 ka. 26Al/10Be ratios vary between 3.53 ± 0.20 and 7.01 ± 0.32, and many of these ratios indicate complex exposure histories. In contrast, among nine in-situ 14C exposure ages, five vary between 4.2 ± 0.1 and 22.0 ± 1.3 ka, and four are saturated. We conclude that the accumulation of these blue ice moraines commenced before or during the global Last Glacial Maximum. Our results indicate that surficial sediment sources can yield exposure ages that are older than real exposure age, and exhibit a wider scatter. This can alter the reconstructed chronology of these landforms. The analysis of in-situ 14C has a high potential in tracking the pace of their evolution, especially since the Last Glacial Maximum. ISSN:2666-0334